Issues in corporate governance - Alo, Oladimeji (Lagos, Nigeria : Financial Institutions Training Centre, 2003)
The book covers the concepts, definitions, best practices, and local and international dimensions of corporate governance.
Includes index.
rua 25/02/15
Loans
Keywords: Corporate governance